Oilseeds sector in India: A trade policy perspective - R, RENJINI V; JHA, GIRISH K (The Indian Journal of Agricultural Sciences, 2019)
The government had been intervening in the oilseed sector from time to time in the form of production, price and trade related policies to improve edible oils availability in India. In this paper, we analyse the impact of trade policy measures adopted by the government to improve domestic oilseeds production. A simultaneous equation simulation model was applied to find out the impact of recent import duty hike on palm oil on production and consumption of edible oils in India. The tariff hike will benefit the oilseeds growers through increase in the price of edible oils. The net impact in the economy will be negative due to the higher reduction in consumer surplus that may outweigh the increase in producer surplus and government revenue. The duty hike may yield short term benefit but improvement in yield, proper procurement and strengthening of edible oils processing industries are the keys for long term strategy for revival of the sector.